The Fed's Rate Hike Impact on Stock Volatility: A Comparison of Shariah and Conventional Banks - Sri Anggowati, Luki; Wahyudi, Henri D; Kistiani Hegy Suryana, Alean; Ria Safitri, Unna (Department of Islamic Banking, 2024)
This study investigates the impact of The Fed’s rate hikes on the stock price volatility of conventional and Shariah-compliant banks in Indonesia, with a focus on comparing their responses to global monetary shocks. The research employs GARCH(1,1) models to analyze daily data from January 6, 2021, to August 30, 2024, for BBRI (conventional) and BRIS (Shariah-compliant). Macroeconomic factors such as inflation, BI Rate, and The Fed’s rate hike (dummy variable) are included as external regressors. The results reveal that The Fed’s rate hikes significantly increase the volatility of conventional banks like BBRI, while reducing volatility in Shariah-compliant banks like BRIS. This contrasting behavior reflects the structural differences between the two banking models, with Shariah-compliant banks showing greater resilience due to their reliance on risk-sharing mechanisms and avoidance of interest-based operations. The findings offer valuable insights for investors, policymakers, and financial institutions. For investors, Shariah-compliant banks provide a more stable investment during global monetary tightening. Policymakers can use these insights to develop targeted strategies to enhance financial stability in Indonesia’s dual banking system. This study contributes to the literature by providing a comparative analysis of how conventional and Shariah-compliant banks respond to global monetary policy shocks, highlighting the unique resilience of Islamic financial principles.